Satisfactory short-term outcomes of totally laparoscopic ileostomy reversal compared to open surgery in colorectal cancer patients - Xu, Zheng; Luo, Shou; Su, Hao; Liang, Jianwe; Liu, Qian; Wang, Xishan; Jin, Weisen; Zhou, Haitao (Frontiers in Surgery, 2023)
Background: Recently, totally laparoscopic (TLAP) surgery has suggested its potential on ileostomy reversal. This study aimed to compare the short-term outcomes between TLAP and traditional open ileostomy reversal. Patients and methods: From September 2016 to September 2021, 107 eligible patients underwent TLAP (n=48) or open (n=59) loop ileostomy reversal were retrospectively enrolled. Surgical parameters, postoperative recovery and complications were identified and compared between TLAP technique versus open surgery. Results: The operation time and estimated blood loss showed no obvious difference between TLAP and open group. However, TLAP reversal significantly decreased the incision length (4.5cm vs. 6cm, P<0.001). Furthermore, patients underwent TLAP surgery showed quicker first ground activities (1 day vs. 2 days, P<0.001), faster first flatus passage (2 days vs. 3 days, P=0.004) and shorter postoperative stay (5 days vs. 7 days, P=0.007). More importantly, postoperative complications were significantly reduced after TLAP reversal (3 cases vs 10 cases, P=0.026). Further logistic regression analyses also indicated the TLAP technique was associated with lower incidence of complications (OR=3.316, CI: 1.118-9.835; P=0.031). Conclusions: TLAP surgery is competitive in promoting postoperative recovery as well as reducing complications compared to the traditional open ileostomy reversal.